2011
DOI: 10.1089/jmf.2010.0154
|View full text |Cite
|
Sign up to set email alerts
|

Oral Consumption of Cranberry Juice Cocktail Inhibits Molecular-Scale Adhesion of Clinical UropathogenicEscherichia coli

Abstract: Cranberry juice cocktail (CJC) has been shown to inhibit the formation of biofilm by uropathogenic Escherichia coli. In order to investigate whether the anti-adhesive components could reach the urinary tract after oral consumption of CJC, a volunteer was given 16 oz of either water or CJC. Urine samples were collected at 0, 2, 4, 6, and 8 hours after consumption of a single dose. The ability of compounds in the urine to influence bacterial adhesion was tested for six clinical uropathogenic E. coli strains, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 40 publications
0
52
0
3
Order By: Relevance
“…In addition to studies with juice, the urine of volunteers who have consumed CJC has been investigated to determine if anti-adhesive or anti-biofilm compounds remain in urine. We previously reported that AFM adhesion force measurements between uropathogenic E. coli were decreased in the presence of urine from a volunteer who had consumed CJC [18]. In addition, DiMartino et al showed that cranberry juice consumption decreased biofilm development of uropathogenic E. coli in the urine compared with placebo [19,20].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition to studies with juice, the urine of volunteers who have consumed CJC has been investigated to determine if anti-adhesive or anti-biofilm compounds remain in urine. We previously reported that AFM adhesion force measurements between uropathogenic E. coli were decreased in the presence of urine from a volunteer who had consumed CJC [18]. In addition, DiMartino et al showed that cranberry juice consumption decreased biofilm development of uropathogenic E. coli in the urine compared with placebo [19,20].…”
Section: Introductionmentioning
confidence: 95%
“…Bacteria were immobilized to acid-cleaned glass slides using a cross-linking reaction between amine and carboxyl groups [18]. The cleaned glass slides were immersed in 10% 3-aminopropyltrimethoxysilane in methanol for 20 min.…”
Section: Bacterial Cell Preparation For Afmmentioning
confidence: 99%
“…6,7,[12][13][14] The anti-adhesive properties of cranberries are effective against the ubiquitous and comparatively benign E. coli with type-1 fimbriae, as well as against p-fimbriated and antibioticresistant E. coli strains. [14][15][16] Incubation of p-fimbriated E. coli with cranberry juice of neutral pH changes the conformation of surface molecules on p-fimbriae within 2 hours profoundly and the adhesion power gets lost. 17 The conclusion of cranberries as harboring potent anti-adhesive compounds other than fructose had fueled a lively research to identify them.…”
Section: Anti-adhesion Effects As Putative Anti-infective Mechanismmentioning
confidence: 99%
“…This is reasonable, as there is strong evidence for cranberry-restricted A-type PAC as anti-adhesive compounds, sufficient evidence for PAC bioavailability in humans [29][30][31] and the preservation of anti-adhesive activity in the urine after oral ingestion. 14,16 Consequently, recently performed clinical trials have employed cranberry products standardized for their PAC, sometimes even for their A-type PAC content to deliver enough bioactivity to probands or patients. However, the ingested dose of PAC/A-type PAC necessary to inhibit bacterial adhesion in the urine is still unknown.…”
Section: Anti-adhesion Effects As Putative Anti-infective Mechanismmentioning
confidence: 99%
See 1 more Smart Citation